Realizing controllable graphene nucleation by regulating the competition of hydrogen and oxygen during chemical vapor deposition heating. Issue 34 (10th August 2016) - Zhang, Haoran; Zhang, Yaqian; Zhang, Yanhui; Chen, Zhiying; Sui, Yanping; Ge, Xiaoming; Deng, Rongxuan; Yu, Guanghui; Jin, Zhi; Liu, Xinyu
Abstract : Controllable graphene nucleation on a CuO/Cu substrate can be realised by adjusting the hydrogen introduction temperature. Abstract : Oxygen can passivate Cu surface active sites when graphene nucleates. Thus, the nucleation density is decreased. The CuO/Cu substrate was chosen for graphene domain synthesis in our study. The results indicate that the CuO/Cu substrate is beneficial for large-scale, single-crystal graphene domain synthesis. Graphene grown on the CuO/Cu substrate exhibits fewer nucleation sites than on Cu foils, suggesting that graphene follows an oxygen-dominating growth. Hydrogen treatment via a heating process could weaken the surface oxygen's role in limiting graphene nucleation under the competition of hydrogen and oxygen and could transfer the synthesis of graphene into a hydrogen-dominating growth. However, the competition only exists during the chemical vapor deposition heating process. For non-hydrogen heated samples, oxygen-dominating growth is experienced even though the samples are annealed in hydrogen for a long time after the heating process. With the temperature increases, the role of hydrogen gradually decreases. The balance of hydrogen and oxygen is adjusted by introducing hydrogen gas at a different heating temperatures. The oxygen concentration on the substrate surface is believed to determine the reactions mechanisms based on the secondary ion mass spectrometry test results. This study provides a new method for the controllable synthesis of graphene nucleation during a heating process.